Deepfake Disinformation By Political Buzzers: Analysis Of The Implications For Civil Liberties In The “Ibu Jilbab Pink” Case - Nailah Alifah Mujahidah; Lia Wulandari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The increasing sophistication of digital media manipulation has intensified the spread of political disinformation, presenting new challenges for civil liberties in digital public spaces. This study examines the implications of deepfake disinformation about "Ibu Jilbab Pink" disseminated by political buzzers on Instagram during the August-September 2025 movement for citizens' civil liberties in Indonesia's digital public sphere. Using a qualitative case study approach that combines netnographic observation of 15 purposively selected Instagram content units with in-depth expert interviews, the analysis identifies three dominant narrative constructions: symbolic delegitimization, identity delegitimization, and public polarization. The findings indicate that political buzzers systematically employed deepfake-based disinformation to undermine both the individual figure and the symbolic meaning of collective protest, thereby narrowing citizens' freedom of expression, weakening deliberative discourse, and suppressing civic participation. The study concludes that deepfake disinformation may function as an instrument of refeudalization, as theorized by Habermas, with implications that extend beyond the individual figure to the broader civil and political citizenship of the public she represented.